Significant improved quantum yields of CaAl12O19:Mn4+ red phosphor by co-doping Bi3+ and B3+ ions and dual applications for plant cultivations - Zhu, Yuejun; Qiu, Zhongxian; Ai, Bingyan; Lin, Yiting; Zhou, Wenli; Zhang, Jilin; Yu, Liping; Mi, Qinghua; Lian, Shixun (Journal of luminescence, 2018)
CaAl12O19: Mn4+ has been reported as a red phosphor with good color purity. A quaternary-doping strategy was adopted to improve the optical properties in this work. Phosphors of general formula Ca1-mAl12-x-y-nO19: xMn4+, yMg2+, mBi3+, nB3+ (CAO:MMBB) were synthesized by high-temperature solid-state method. A broad band deep-red emission from Mn4+ centered at 654 nm was observed, and two strong absorption bands within the ultraviolet range (350–400 nm) and blue-green region peaked at 460 nm were confirmed. The incorporation of co-dopants brought about a remarkable enhancement of the luminescence intensity. The quantum yield of CAO:MMBB reached 84.9%, which is approximately 1.35 times higher than that of as-reported binary-doping phosphors CaAl12-x-yO19: xMn4+, yMg2+ (CAO:MM). The possible mechanism of co-doping Bi3+ and B3+ ions was discussed in detailed. CAO:MMBB phosphor shows a dual application in agriculture either as solar spectral conversion auxiliary in greenhouse plastic films or as a red component in blue-chip based plant growth light emitting diodes (PG-LEDs). The quaternary-doped phosphors CaAl12O19: Mn4+, Bi3+, Mg2+, B3+ (CAO:MMBB) were designed and synthesized. The synergetic effect of Bi3+ and B3+ leads to high quantum yields (84.9%) of deep-red emission originating from Mn4+ ion 3d3 transitions in octahedral symmetry. The fabrication of solar spectral conversion (SSC) films and plant growths (PG) LEDs added CAO:MMBB show excellent dual applications in plant cultivations. [Display omitted]